Tingkat organizational citizenship behavior guru bimbingan dan konseling - Azizha Finanda P.; Dian Renata; Hengki Satrianta (Orien: Cakrawala Ilmiah Mahasiswa, 2023)
the aim of this study was to describe the level of organizational citizenship behavior in Guidance and Counseling teachers. This study is a quantitative research with a survey type. This research was conducted on teachers at the senior high school and state vocational high schools in Kendari City. This research is a population study so that a total of 60 Guidance and Counseling teachers at the senior high school and state vocational high schools in Kendari City are the sample in this study. Data is collected through the organizational citizenship behavior scale. Data were analyzed descriptively using percentage analysis. The results of the study concluded that the level of organizational citizenship behavior of Guidance and Counseling teachers is in the medium category. Efforts are needed to improve organizational citizenship behavior in Guidance and Counseling teachers.